2002
DOI: 10.1523/jneurosci.22-14-05833.2002
|View full text |Cite
|
Sign up to set email alerts
|

Limbic Seizures Induce P-Glycoprotein in Rodent Brain: Functional Implications for Pharmacoresistance

Abstract: The causes and mechanisms underlying multidrug resistance (MDR) in epilepsy are still elusive and may depend on inadequate drug concentration in crucial brain areas. We studied whether limbic seizures or anticonvulsant drug treatments in rodents enhance the brain expression of the MDR gene (mdr) encoding a permeability glycoprotein (P-gp) involved in MDR to various cancer chemotherapeutic agents. We also investigated whether changes in P-gp levels affect anticonvulsant drug concentrations in the brain. Mdr mRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

14
188
2
4

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 226 publications
(208 citation statements)
references
References 41 publications
14
188
2
4
Order By: Relevance
“…In mice, increased expression of ABCB1 mRNA was noted as early as 3 h after Ն90 min of recurrent seizures, and when tested at 6 h, increased ABCB1 levels were associated with significantly lower hippocampal PHT levels (9). In rats, increased ABCB1 levels in hippocampal astrocytes were noted by 24 h after kainate injection (15).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…In mice, increased expression of ABCB1 mRNA was noted as early as 3 h after Ն90 min of recurrent seizures, and when tested at 6 h, increased ABCB1 levels were associated with significantly lower hippocampal PHT levels (9). In rats, increased ABCB1 levels in hippocampal astrocytes were noted by 24 h after kainate injection (15).…”
Section: Discussionmentioning
confidence: 96%
“…Thus members of the ABC superfamily ABCB1 (also known as MDR1 P-glycoprotein) and ABCC1 (also known as multidrug resistanceassociated protein 1) are upregulated in glia and neurons in resected and postmortem human brain tissue containing pathologies causing refractory epilepsy (1)(2)(3)(4)(5)(6). In animal studies, both ABCB1 and ABCC1 have been shown to transport a variety of AEDs, including phenytoin (PHT) (1,(7)(8)(9), phenobarbitone (PB) (10), carbamazepine (CBZ) (8,9), lamotrigine (LTG), topiramate (TPM), and felbamate (FBM) (8,11). Other AEDs are likely to be ABCB1 substrates, as most AEDs share a planar lipophilic chemical structure.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…13) After intraloop administration, the brain CBZ and its active metabolite CBZ-epo concentrations in KA-treated mice were significantly retarded as compared to the control mice, and no significant decrease was found in plasma CBZ and CBZ-epo in the portal vein (Fig. 1).…”
Section: Discussionmentioning
confidence: 92%
“…1,13) However, there has been no clear answer to explain the mechanism in the relationship between invagination of epileptic fit and CBZ efficacy. On the other hand, P-gp, which locates on the inside cells of capillary vessel of blood-brain barrier (BBB), regulates the transfer of drug from blood circulation to the central nerve system to avoid neurotoxicity.…”
Section: Discussionmentioning
confidence: 99%